Magyaroszág és az Európai Unió a sajtó tükrében: Egy tartalomelemzéses vizsgálat eredményei - Terestyéni, Tamás (Szociológiai Szemle, 2024)
In order to learn how the most influential Hungarian press organs depict the European Union and Hungary's accession to integration, in 2000 a content analysis was made on a large sample of the Hungarian national and local newspapers. The analysis confirmed the results of several public opinion polls and other studies indicating that among the most determinant groups of the Hungarian society there are no considerable opponents to accession. The largest part of the qualitative press items argued in favour of the EU and Hungary's accession, and no serious arguments against a rapid integration were to be found. According to the press, both Hungarian and Western European sources agreed that Hungary made good progress in the preparation for accession, nevertheless many articles called attention to the requirements the country has to meet, especially the problems of agriculture, environment and labour force were emphasised. Although the basic message of the press was optimistic, some news items and commentaries expressed ambivalence and vagueness in respect of the (political) decision makers' intentions.